2020
DOI: 10.1002/pca.2933
|View full text |Cite
|
Sign up to set email alerts
|

Detecting kinsenoside from Anoectochilus roxburghii by HPLC‐ELSD with dual columns of NH2 and AQ‐C18

Abstract: Introduction: Kinsenoside is a characteristic component of Anoectochilus roxburghii and accounts for this herb's medicinal and edible values. No international certified standard method is available for kinsenoside analysis as well as extraction and preservation. Objective: To develop a more accurate analytical method of kinsenoside. The effects of extraction and drying methods of A. roxburghii on kinsenoside efficiency were investigated for the first time, as well as to examine the kinsenoside stability. Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Phytochemical investigations have revealed that AR is rich in various functional components, such as kinsenoside, polysaccharides, flavonoids, glycosides, organic acids, steroids, triterpenes, and alkaloids [9,10]. AR has many pharmacological activities, including antidiabetic [11], blood vessel protection [12], liver protection [13], antioxidant [14], antibacterial [15], and anticancer effects [16]. In recent years, AR has been widely used in medicine, functional foods, beauty, and other fields and is considered one of the most valuable medicinal plants.…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical investigations have revealed that AR is rich in various functional components, such as kinsenoside, polysaccharides, flavonoids, glycosides, organic acids, steroids, triterpenes, and alkaloids [9,10]. AR has many pharmacological activities, including antidiabetic [11], blood vessel protection [12], liver protection [13], antioxidant [14], antibacterial [15], and anticancer effects [16]. In recent years, AR has been widely used in medicine, functional foods, beauty, and other fields and is considered one of the most valuable medicinal plants.…”
Section: Introductionmentioning
confidence: 99%